(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
In the article an annotated list of the flora of vascular plants is presented for the forested part of the Burkuty Plavni natural landmark. The landmark occupies an area of 350 ha in the Chalbasska arena of the Nyzhnodniprovski pisky (Lower Dnipro Sands), near the small village Burkuty (Hola Prystan district, Kherson region). The list includes 425 species belonging to 252 genera, 75 families, 5 classes and 4 divisions. Among them, 247 species have been found for the first time in the landmark. However, we did not find 21 species, identified in the landmark earlier. The favored conditions for growth, frequency of occurrence, sozological status, and relevant, earlier references in the literature have been indicated for each species identified in the present study. The flora of the forested part of the landmark is unique in that it has a high degree of species diversity (48.1% of the flora of the Lower Dnipro sand area), though it only occupies 0.22% of the whole territory. There are 25 sozophytes among the flora (5.9 %). Another reason for the high sozological value of the flora of the Burkuty Plavni natural landmark is the mix of endemic plants and the significant share of boreal plants in their composition, i.e. northern species on the southern boundary of their range. At the present moment only a part of the landmark is included in the Oleshkivski Pisky National Nature Park (50 ha, or 14.3%). As a result, 264 species (62,1%) of the landmark flora, including seven sozophytes (Ceratophyllum tanaiticum, Dactylorhiza incarnata, Dryopteris carthusiana, Polygonatum odoratum, Potamogeton sarmaticus, Salvinia natans, Stachys officinalis) are not currently protected. These results convincingly show the inadequate protection of the floristic biodiversity of the landmark at the present stage. It is thus important to include the entire Burkuty Plavni in the Oleshkivski Pisky National Nature Park thereby protecting its important biodiversity.